Cardiac wasting in head and neck cancer and in cardiac autopsies from different cancer types: A study in a chemo‐naïve setting - Sara Calamelli; Samantha Noto; Alessandra Baldoni; Alessandra Casarin; Alessandro Calzavara; Irene Bolgan; Silvia Coccato; Salvatore Saccà; Licia Laurino; Giuseppe Azzarello; Simonetta Ausoni (Journal of Cachexia, Sarcopenia and Muscle, 2023)
Abstract Background Cardiac wasting is a detrimental consequence of cancer that has been traditionally ignored and often misinterpreted as an iatrogenic effect. Methods We conducted a retrospective study on 42 chemo‐naive patients affected by locally advanced head and neck cancer (HNC). Based on unintentional weight loss, patients were divided into cachectic and non‐cachectic. Left ventricular mass (LVM), LV wall thickness (LVWT), interventricular septal (IVS) thickness, left ventricular internal diameter diastolic (LVIDd), left ventricular internal diameter systolic (LVIDs), internal ventricular septum diastolic (IVSd), left ventricular posterior wall thickness diastolic (LVPWd) and LV ejection fraction (LVEF) were analysed by echocardiography. In parallel, we retrospectively analysed 28 cardiac autoptic specimens of patients who either died of cancer before chemotherapy or with a diagnosis of cancer at autopsy. Presence or absence of myocardial fibrosis at microscopic observation was used for sample stratification. Conventional histology was performed. Results Cachectic and non‐cachectic patients had a significantly different value of LVWT and IVS thickness and LVPWd. LVWT was 9.08 ± 1.57 versus 10.35 ± 1.41 mm (P = 0.011) in cachectic and non‐cachectic patients, IVS was 10.00 mm (8.50–11.00) versus 11.00 mm (10.00–12.00) (P = 0.035), and LVPWd was 9.0 (8.5–10.0) and 10.00 mm (9.5–11.0) (P = 0.019) in cachectic and non‐cachectic patients. LVM adjusted for body surface area or height squared did not differ between the two populations. Similarly, LVEF did not show any significant decline. At multivariate logistic regression analysis for some independent predictors of weight loss, only LVWT maintained significant difference between cachectic and non‐cachectic patients (P = 0.035, OR = 0.240; P = 0.019). The secondary analysis on autoptic specimens showed no significant change in heart weight, whereas LVWT declined from 9.50 (7.25–11.00) to 7.50 mm (6.00–9.00) in cardiac specimens with myocardial fibrosis (P = 0.043). These data were confirmed in multivariate logistic regression analysis (P = 0.041, OR = 0.502). Histopathological analysis confirmed severe atrophy of cardiomyocytes, fibrosis and oedema as compared with controls. Conclusions Subtle changes in heart structure and function occur early in HNC patients. These can be detected with routine echocardiography and may help to select appropriate cancer treatment regimens for these patients. Histopathological analysis provided conclusive evidence that atrophy of cardiomyocytes, oedema and fibrosis occur during cancer progression and may precede the onset of overt cardiac pathology. To our knowledge, this is the first clinical study that establishes a direct relationship between tumour progression and cardiac remodelling in HNCs and the first pathological study conducted on human cardiac autopsies from selected chemo‐naïve cancer patients.